PROCESS OF SUGARCANE HARVESTING BY MIGRANT LABOURERS (International Journal of Food and Nutritional Sciences, 2022)
Migration plays an important role in the distribution of population of any society and influences the growth of work force or laoburers. It bears influence on the socio-economic changes among the migrated workers. Most of these workers migrate because of necessity rather than a choice. These migrated labourers can earn more and might get better education for their children. Moreover, large number of children are being affected by seasonal labour migration. Children who are left behind or who migrate with their parents face many problems in terms of education and health care. They also suffer from various psycho-social issues are exposed to exploitation. Seasonal migration and employment of destination have a number of effects on the sugarcane harvesters as well as on their dependents. Such consequences have both positive as well as negative effects on them. The consequence on sugarcane harvesters is both economic and social in nature. From social viewpoint seasonal migration can spark off social and educational changes in the family of sugarcane harvesters. To meet their needs and achieve better future they have to work longer and harder. These workers are not covered by any of the existing labour laws and legislations. Hence they face the problem of job security and social protection. They do not have stable employment and employee and employer relationship does not exist formerly.